Anti-Inflammatory Properties of Drugs from saffron crocus - Poma, Anna; Fontecchio, Gabriella; Carlucci, Giuseppe; Chichiricco, Giuseppe (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2012)
The medicinal uses of saffron (Crocus sativus Linnaeus) have a long history beginning in Asian countries since the Late Bronze Age. Recent studies have validated its potential to lower the risk of several diseases. Some metabolites derived from saffron stigmas exert numerous therapeutic effects due to hypolipidemic, antitussive, antioxidant, antidiabetic activities and many others. Water and ethanol extracts of Crocus sativus L. are cardioprotective and counteract neurodegenerative disorders. Many of these medicinal properties of saffron can be attributed to a number of its compounds such as crocetin, crocins and other substances having strong antioxidant and radical scavenger properties against a variety of radical oxygen species and pro-inflammatory cytokines. Botany, worldwide spreading of cultivars, biochemical pathways, active constituents and chemical detection methods are reviewed. Therapeutic uses of saffron principles with particular regard to those exhibiting antioxidant and thus anti-inflammatory features are discussed. To date, very few adverse health effects of saffron have been demonstrated. At high doses (more than 5 g/die day), it should be avoided in pregnancy owing to its uterine stimulation activity.
Keywords: DNA damages